The Relationship between Energy Inflation and Exchange Rate: A Study on Türkiye - ÇELİK, Mehmet Yunus; DANIŞOĞLU, Faik (Journal of the Human and Social Sciences Researchers, 2023)
Energy is among the indicators that are taken into consideration in increasing the production levels of countries and increasing their welfare. Energy has become an indispensable resource for the industrialization of countries, increasing their industrial production and ensuring their development and growth in this direction. Today, the development and growth of countries have become linked to their energy consumption. However, countries that lack energy resources need to import the energy resources they need in order to realize their development and growth, and their economic activities for this purpose are closely related to other economic indicators, especially the exchange rate, and bring about a series of economic results. This study examines the existence of the relationship between energy inflation and the real exchange rate in Türkiye in light of the fact that Türkiye is heavily dependent on foreign energy consumption. Accordingly, the study utilizes monthly series of energy inflation and real exchange rate variables for the period 2012:M01-2021:M12 for Türkiye. In the study, firstly, the series of the variables are seasonally adjusted with the help of a computer package program, then the variables are logarithmically transformed and the stationarity of the series of the variables is analyzed. According to the results of ADF and PP unit root tests, it is concluded that the series of energy inflation and real exchange rate variables are not stationary at level, but both series become stationary after first differences are taken. In the study, Engle-Granger cointegration analysis was conducted in accordance with the unit root test results. According to the results of cointegration analysis, energy inflation and real exchange rate variables are found to move together in the long run. Finally, Granger causality test analysis was conducted and according to the results of this analysis, the existence of bidirectional causality in the Granger sense between energy inflation and real exchange rate was determined.
Keywords: İktisat; 11. Sustainability; 8. Economic growth; 1. No poverty; 7. Clean energy